Behavior, growth, and reproduction of Lumbriculus variegatus (Oligochaetae) in different sediment types - Sardo, A. M.
Lumbriculus variegatus is an oligochaete widely used in sediment toxicity tests. The locomotory behavior of adults from a normal and a clone population was studied in the Multispecies Freshwater Biomonitor (TM) along with growth and reproduction to determine how different sediment types may affect this worm and forced clones during testing. Four different sand size classes were established by sieving: fine (< 1 mm), medium (1 < x < 2 mm), coarse (> 2 mm), and whole sediment. Locomotory activity was highest in fine and then in coarse sediment, while in whole and medium sediment size classes worms grew and reproduced less, and had lower locomotory activity levels. Fine sediment (< 1 mm) should be used as the negative control in L. variegatus whole sediment toxicity tests. A clone population, generated by cutting all worms over six generations, showed lower locomotory activity levels than normal worms. Artificial cloning is not recommended for obtaining additional test organisms.